Spiritual Talk: Addressing Existential Themes in Interfaith Encounters - Liefbroer, Anke I. (International journal of practical theology, 2020)
Spiritual caregivers increasingly care for clients with other religious/spiritual (R/S) orientations than their own. To date, the ways in which spiritual caregivers deal with these differences have hardly been explored. Based on an analysis of audio records of 34 spiritual caregiver-patient interactions, this paper describes communication techniques used by spiritual caregivers to address existential themes in conversations with patients with various R/S orientations. The model presented describes these techniques regarding the extent to which spiritual caregivers comply with the patient’s R/S orientation and disclose their own R/S orientation. This model can be used to analyze how spiritual caregivers interact with their clients.